2020
DOI: 10.3390/life10070107
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Viral Abundance and Community Composition in Four Contrasting Regions of the Southern Ocean

Abstract: We explored how changes of viral abundance and community composition among four contrasting regions in the Southern Ocean relied on physicochemical and microbiological traits. During January–February 2015, we visited areas north and south of the South Orkney Islands (NSO and SSO) characterized by low temperature and salinity and high inorganic nutrient concentration, north of South Georgia Island (NSG) and west of Anvers Island (WA), which have relatively higher temperatures and lower inorganic nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 95 publications
1
8
0
Order By: Relevance
“…The assessment of environmental drivers of community structure demonstrates that the temperature variable exhibited the highest positive correlation (Mantel r statistic = 0.56, P < 0.001) followed by the oceanic region (Mantel r statistic = 0.23, P < 0.001). This pattern also agrees with that observed at the SO intraregional level, where temperature appears as the primary determinant of variability among viral communities ( 44 ). Subsequently, we hypothesize that present-day SO viruses arose via the strong environmental selective pressures of the SO region and the low gene flow associated with the circumpolar current.…”
Section: Resultssupporting
confidence: 90%
“…The assessment of environmental drivers of community structure demonstrates that the temperature variable exhibited the highest positive correlation (Mantel r statistic = 0.56, P < 0.001) followed by the oceanic region (Mantel r statistic = 0.23, P < 0.001). This pattern also agrees with that observed at the SO intraregional level, where temperature appears as the primary determinant of variability among viral communities ( 44 ). Subsequently, we hypothesize that present-day SO viruses arose via the strong environmental selective pressures of the SO region and the low gene flow associated with the circumpolar current.…”
Section: Resultssupporting
confidence: 90%
“…In addition, polar SML viral and microbial communities are subjected to stronger gradients of salinity and ambient temperature, as well as to episodes of strong wind and higher UV radiation along with extended photoperiods than those in lower latitudes. Furthermore, the ranges of temperature (higher in the Arctic) and other environmental variables such as salinity, organic nutrients, and inorganic nutrients may differ between Arctic and Antarctic waters [ 18 , 19 ], possibly resulting in different dynamics of the viral and microbial communities in the SML of these two polar areas.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, low temperatures in polar environments do not inhibit viral activity and its potential to infect microbial communities (Anesio and Bellas, 2011). It has been observed that in Antarctic and Sub-Antarctic marine environments viral abundance is primarily related to temperature (Sotomayor-Garcia et al, 2020;Figure 2, ID 9-12). Furthermore, in areas surrounding the Antarctic peninsula (Vaqué et al, 2017;Figure 2, ID 13-15) viruses rather than grazers are more important agents of prokaryotic mortality.…”
Section: Influence Of Environmental Variables On the Viral Dynamics I...mentioning
confidence: 99%
“…Furthermore, in areas surrounding the Antarctic peninsula (Vaqué et al, 2017;Figure 2, ID 13-15) viruses rather than grazers are more important agents of prokaryotic mortality. In addition, in our database, the relationship between VPR and temperature may be influenced by the data obtained from the areas studied in the Southern Ocean (Vaqué et al, 2017;Sotomayor-Garcia et al, 2020), where viral activity and prokaryotic production is more affected by temperature than by any other environmental factors. It is worth mentioning that viruses are resilient to low temperatures, since when weather conditions are unfavorable for prokaryotes growth, viruses change their lytic life strategy for a lysogenic one (Laybourn-Parry et al, 2007;Anesio and Bellas, 2011;Brum et al, 2017).…”
Section: Influence Of Environmental Variables On the Viral Dynamics I...mentioning
confidence: 99%